Cover JGEET Vol 03 No 01 2018 - (J. Geoscience Eng. Environ. Technol), JGEET (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
This Volume Consists of Research Article as follow: Experimental Study to Reinforce The Weak Subgrade Soil For Low-Volume Roads by Coir Geotextile Mats Fluid Inclusion Study of The Tumpangpitu High Sulfidation Epithermal Gold Deposit in Banyuwangi District, East Java, Indonesia Modified Soil-Adjusted Vegetation Index In Multispectral Remote Sensing Data for Estimating Tree Canopy Cover Density at Rubber Plantation A Study On Influence Of Real Municipal Solid Waste Leachate On Properties Of Soils In Warangal, India Halogen Chemistry of Hydrothermal Micas: a Possible Geochemical Tool in Vectoring to Ore for Porphyry Copper-Gold Deposit The Phenomena of Flood Caused by the Seawater Tidal and its Solution for the Rapid-growth City: A case study in Dumai City, Riau Province, Indonesia Spatial Statistical Analysis for Potential Transit Oriented Development (TOD) in Jakarta Metropolitan Region Infiltration Rate of Quarternary Sediment at Rumbio Jaya, Kampar, Riau Quaternary Sediment Characteristic of Floodplain Area: Study Case at Kampar River, Rumbio Area and Surroundings, Riau Province